Gharar In Digital Economic Transactions: A Qualitative Analysis of E-Commerce Practices - Adel, Ichsanul Reihan; Rinaldi, Afdhol (JAWI : Journal of Ahkam Wa Iqtishad, 2024)
The development of digital technology has changed e-commerce transactions, where uncertainty in transactions has become an important issue in Islamic economics. This research aims to analyze the form of gharar in e-commerce and find solutions based on sharia principles. The method used is a literature study with a descriptive approach, and data is collected from secondary sources such as books and journals. The research results show that gharar often appears in the form of unclear product descriptions, non-conformity of goods, and non-transparent return policies, which have a negative impact on consumer trust. The recommended solution is to increase information transparency and improve return policies on e-commerce platforms. Technology such as blockchain can be a solution to reduce gharar and create a fair e-commerce ecosystem according to sharia principles.